Florensky - Gaspare Mura (Critical Hermeneutics, 2024)
This article traces Florensky’s intellectual biography. The author underlines that, more than his numerous scientific, philosophical, theological, mystical works, his most important and imperishable message is the heroic elevation of his Christian testimony in the gulag. Florensky transfigures the “night” with the achievement of a higher spiritual dimension, which he calls “the art of gratuitousness”, of the pure disinterested gift of oneself to God and others, that gratuitousness which is synonymous with grace and beauty.